2019
DOI: 10.1021/acssuschemeng.9b00097
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of CaTi1–xMnxO3–δ-Based Photocatalyst for Photocatalytic Reduction of NO via Structure-Reforming of Ti-Bearing Blast Furnace Slag

Abstract: In this work, a novel low-cost and robust approach is developed to covert Ti-bearing blast furnace slag (Ti-slag) to the main feed stock of photoassisted NH3 selective catalytic reduction (Photo NH3-SCR) of NO with high performance. The CaTi1–x Mn x O3−δ catalyst was directly extracted from the Ti-bearing slag with MnO2 in situ modification and Na2CO3 reformation followed by dilute hydrochloric acid leaching and water washing. Various methods were employed to characterize the structure changes of the slag in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…However, while the narrow band gap increases the usage of visible light, it is also accompanied by the rapid recombination of photo-generated electrons and holes. The low photocatalytic efficiency restricts pure MnO 2 for practical applications [37][38][39] .Coupling MnO 2 with other semiconductors to build a heterojunction is an effective method to prevent the recombination of photo-generated carriers. Wang et al 40 first reported that g-C 3 N 4 could decompose water to generate hydrogen by visible light irradiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, while the narrow band gap increases the usage of visible light, it is also accompanied by the rapid recombination of photo-generated electrons and holes. The low photocatalytic efficiency restricts pure MnO 2 for practical applications [37][38][39] .Coupling MnO 2 with other semiconductors to build a heterojunction is an effective method to prevent the recombination of photo-generated carriers. Wang et al 40 first reported that g-C 3 N 4 could decompose water to generate hydrogen by visible light irradiation.…”
mentioning
confidence: 99%
“…However, while the narrow band gap increases the usage of visible light, it is also accompanied by the rapid recombination of photo-generated electrons and holes. The low photocatalytic efficiency restricts pure MnO 2 for practical applications [37][38][39] .…”
mentioning
confidence: 99%
“…TiO 2 is one of the most common photocatalysts; it has good performance in many photocatalytic applications, such as water splitting, hydrogen production, carbon dioxide reduction, nitrogen oxide reduction, nitrogen xation, pollutant degradation, organic reactions, and ammonia synthesis and decomposition. 31,42,[65][66][67][68][69][70][71][72][73][74] Three crystal types of TiO 2 , including anatase type, rutile type and plate titanium type, exist in nature, with bandgap widths of 3.0, 3.2 and 3.25 eV, respectively. 75 Bare TiO 2 shows lower photocatalytic activity in ammonia decomposition due to the reactive energy barrier.…”
Section: Metal-loaded Tio 2 and Its Heterojunction Photocatalystsmentioning
confidence: 99%
“…The ineffective use of Ti-bearing blast furnace slag wastes Ti resources and causes environmental pollution. 4 Many methods have been proposed for the clean utilization of Ti-bearing blast furnace slag, which include two routes: non-Ti extraction and Ti extraction. In non-Ti extraction routes, Ti-bearing blast furnace slag can be used as a photocatalytic degradation material, 5 compound fertilizer, 6 foam glass-ceramic, 7 and building materials (concrete 8 and sintered slag bricks 9 ); however, the most valuable element in Ti-bearing blast furnace slag, Ti, is not utilized effectively, and much of it is wasted; therefore, to make better use of Ti, the extraction of Ti from Ti-bearing blast furnace slag has been investigated.…”
Section: Introductionmentioning
confidence: 99%